Honey Purity Analysis of Trigona sp. species in Royal Honey Sakah, Bali - Ni Wayan Susilawati; Ni Luh Gede Sudaryati; I Putu Sudiartawan (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Honey is a sweet liquid produced by bees and derived from the nectar of flowers. The increasing circulation of fake honey has alarmed the public. An analysis of the purity of honey still needs to be reported. This study aimed to analyze the purity of honey from Trigona sp. at Royal Honey Sakah. The qualitative design was used during the study in May 2022 at Royal Honey Sakah. Three honey samples from different bees were analyzed to determine how much water, sugar, and viscosity they had. Our findings show that the purity of honey depends on moisture content, sugar content, and viscosity and that these three parameters depend on the quality of nectar produced from flower plants around the place of cultivation. The purity level in sugar, water, and viscosity content in three types of honey, including Apis dorsata honey, wild forest honey (Tetragonula biroi), and tenganan local honey (Apis sp.), all meet the quality requirements of honey according to SNI 8664: 2018. Therefore, the higher the sugar concentration, the less water there is in the honey, and the higher the viscosity, the more pure or authentic the honey is. People who will consume honey are expected to be able to identify the quality of honey in terms of its viscous structure, no bubbles resembling heated sugar, and a dark brown or concentrated color. Honey is declared pure if there is no further processing other than filtering from the source.